2015
DOI: 10.1021/acs.analchem.5b03232
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Discovery and Development of a Multiplexed Targeted MRM-LC-MS/MS Assay for Urine Biomarkers of Extracellular Matrix Disruption in Mucopolysaccharidoses I, II, and VI

Abstract: The mucopolysaccharidoses (MPS) are lysosomal storage disorders that result from defects in the catabolism of glycosaminoglycans. Impaired muscle, bone, and connective tissue are typical clinical features of MPS due to disruption of the extracellular matrix. Markers of MPS disease pathology are needed to determine disease severity and monitor effects of existing and emerging new treatments on disease mechanisms. Urine samples from a small cohort of MPS-I, -II, and -VI patients (n = 12) were analyzed using labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…Kingma et al 27 developed an algorithm to predict clinical severity in MPS I based on genotyping and an optimized IDUA assay, however, this assay is not routinely available. In a preliminary proteomic study, the lysosomal protein b-galactosidase was elevated 3.6-to 5.7-fold in severe but not attenuated MPS I, 28 and 1 study has reported that serum heparin-cofactor IIthrombin complex levels can differentiate patients with severe MPS I from patients with attenuated MPS I. 29 Neither of these studies evaluated the utility of these biomarkers in the neonate or early infant, and, thus, their utility for use in NBS is limited.…”
Section: Lack Of Routine Biochemical Markersmentioning
confidence: 95%
“…Kingma et al 27 developed an algorithm to predict clinical severity in MPS I based on genotyping and an optimized IDUA assay, however, this assay is not routinely available. In a preliminary proteomic study, the lysosomal protein b-galactosidase was elevated 3.6-to 5.7-fold in severe but not attenuated MPS I, 28 and 1 study has reported that serum heparin-cofactor IIthrombin complex levels can differentiate patients with severe MPS I from patients with attenuated MPS I. 29 Neither of these studies evaluated the utility of these biomarkers in the neonate or early infant, and, thus, their utility for use in NBS is limited.…”
Section: Lack Of Routine Biochemical Markersmentioning
confidence: 95%
“…As for MPSs, ideal biochemical biomarkers would be specific to a particular type or group of MPSs, help to discriminate more severe from less severe phenotypes, correlate with neurological involvement, respond to therapy, and be easily quantified [244]. In MPSs, primary biochemical biomarkers are represented by the primary storage material; for MPS II, they are partially degraded HS and DS fragments that accumulate in the lysosomes and extracellular matrices (ECM) and are secreted into the bloodstream and then excreted in the urine [245].…”
Section: Disease Biomarkersmentioning
confidence: 99%
“…One key early pathological feature is the disruption of the ECM. [13][14][15] The resulting consequence of this disruption needs to be further understood.…”
Section: Discussionmentioning
confidence: 99%